THE IMPACT THE INFLUENCE OF ISLAMIC BANKING HEALTH LEVEL TO THE LEVEL OF PUBLIC CONFIDENCE WITH THE PERFORMANCE BANKING AS AN INTERVENING VARIABLE : CASE STUDY ON ISLAMIC COMMERCIAL BANKS Period 2017-2021 - Sarah Ramadhani; Hendra Harmain; Nur Ahmadi Bi Rahmani (SEAN Institute, 2023)
This research aims to determine the effect of 1) Risk profile on public trust, 2) Good Corporate Governance on public trust, 3) Earnings on public trust, 4) Capital on public trust and 5) Islamic banking performance on public trust. This research was conducted using a descriptive quantitative method supported by SPSS. For this reason, some important information is generated, namely 1) Risk profile has a negative but significant influence on public trust; 2) positive GCG has a good effect on public trust; 3) Earnings owned by Islamic banks have no influence on public trust; 4) Capital owned by Islamic banks has a connection or influence with public trust; 5) Between the performance of Islamic banking and trust, there is no influence between the two.